2005
DOI: 10.1111/j.1365-3180.2005.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased density and spatial uniformity increase weed suppression by spring wheat

Abstract: It has been hypothesized that increased crop density and spatial uniformity can increase weed suppression and thereby play a role in weed management. Field experiments were performed over 2 years to investigate the effects of the density and spatial arrangement of spring wheat (Triticum aestivum) on weed biomass and wheat yield in weed-infested fields. We used three crop spatial patterns (normal rows, random and uniform) and three densities (204, 449 and 721 seeds m )2 ), plus a fourth density (1000 seeds m )2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
78
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 13 publications
12
78
1
Order By: Relevance
“…Regardless of pretilachlor rate and cultivar, significantly higher grain yields were recorded in plots with uniform planting patterns (3127 kg ha -1 ) compared to the plots with wide-row planting pattern (2588 kg ha -1 ). Similar results were reported for wheat by OLSEN et al (2005), who concluded that there may be other advantages to a uniform planting pattern of the crop in addition to increased weed suppression, such as better absorption of nutrients and utilization of space resources. The interaction between herbicide rate and spatial pattern was not significant for grain yield, indicating that a similar response for grain yield was observed in uniform and row planting pattern to different weed density (due to various application rate of pretilachlor).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Regardless of pretilachlor rate and cultivar, significantly higher grain yields were recorded in plots with uniform planting patterns (3127 kg ha -1 ) compared to the plots with wide-row planting pattern (2588 kg ha -1 ). Similar results were reported for wheat by OLSEN et al (2005), who concluded that there may be other advantages to a uniform planting pattern of the crop in addition to increased weed suppression, such as better absorption of nutrients and utilization of space resources. The interaction between herbicide rate and spatial pattern was not significant for grain yield, indicating that a similar response for grain yield was observed in uniform and row planting pattern to different weed density (due to various application rate of pretilachlor).…”
Section: Resultssupporting
confidence: 84%
“…The use of these machines is increasing because manual transplanting is a labour intensive operation in the cultivation of rice. At the same time, previous studies have shown that crop spatial pattern can affect crop growth, grain yield and herbicide efficacy (OLSEN et al, 2012, OLSEN et al, 2005, WEINER et al, 2001. A recent study, Olsen et al (2012) observed that increased crop uniformity had a negative effect on weed biomass, and concluded that crop pattern effects on weeds occur only through size-asymmetric competition.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Superior weed suppression by spring wheat was found at high seeding density planted in a uniform grid, versus conventional row spacing (Olsen et al 2005a). Subsequent work showed that the more easily achieved random spreading of seed was almost as effective as the uniform grid pattern (Olsen et al 2005b). However, changing planting density and spatial arrangement may have unforeseen consequences.…”
Section: Increasing Crop Competitivenessmentioning
confidence: 99%
“…In general, crop competitive ability can also be increased by improving planting uniformity. Olsen et al (2005a;2005b) reported that wheat produced more biomass and had less weed biomass as crop planting uniformity increased. According to Weiner et al (2001) a more uniform planting distribution should enable crops to compete more successfully with weeds.…”
Section: Introductionmentioning
confidence: 99%